1972
DOI: 10.1111/j.1469-8749.1972.tb02575.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hydrocephalus‐Hydrencephaly in Five Siblings, with Autopsy Studies: a New Disease

Abstract: SUMMARY Following hydramnios, five female arthrorgypotic siblings were born around the 30th week of gestation, labour being further complicated by hydrocephalus. Full autopsy on two babies showed a diffuse destructive process in the brain and spinal cord, resulting in hydren‐cephaly in the forebrain, and gliosis elsewhere, the aqueduct of Sylvius being stenosed to produce hydrocephalus. Striking microscopic changes were the glomeruloid vessels in the brain, spinal cord and retina, and the intracytoplasmic incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 17 publications
3
34
1
Order By: Relevance
“…It is not clear how mutations in FLVCR2 are associated with Fowler syndrome. Fowler syndrome is a recessively inherited lethal disorder characterized by proliferative vasculopathy; brain stem, basal ganglia, and spinal cord ischemic lesions with calcification; and hydranencephaly-hydrocephaly (16). Five affected fetuses from three consanguineous families were found to have a common Thr430Arg mutation in FLVCR2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear how mutations in FLVCR2 are associated with Fowler syndrome. Fowler syndrome is a recessively inherited lethal disorder characterized by proliferative vasculopathy; brain stem, basal ganglia, and spinal cord ischemic lesions with calcification; and hydranencephaly-hydrocephaly (16). Five affected fetuses from three consanguineous families were found to have a common Thr430Arg mutation in FLVCR2.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mutations in the cell surface protein FLVCR2 (MFSD7C), an MFS transporter member, have been shown to be associated with Fowler syndrome (22,26), a proliferative vascular disorder of the brain (16). A previous study (6) suggested that FLVCR2 functions as a calcium-chelate transporter based on its expression in murine and human tissues involved in calcium homeostasis.…”
mentioning
confidence: 99%
“…Analogous to these genetically engineered rodent models, in humans there is a lethal prenatal condition known as proliferative vasculopathy and hydranencephalyhydrocephaly (PVHH), where affected fetuses share several striking similarities with Gpr124 −/− mice, including vascular glomeruloids in both the pallium and ventral spinal cord, enlarged cerebral ventricles, and a thin underdeveloped pallium (36). Although the mutations responsible for PVHH have not yet been identified, these studies suggest that GPR124 might be involved in this or a myriad of other neurovascular diseases associated with BBB breakdown or in the formation of glomeruloids associated with the most malignant forms of glioblastoma and gastrointestinal carcinomas (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…An infectious genesis in the form of fetal encephalitis has been proposed as a possible origin of hydranencephaly [3]. Others attributed the pathologic changes to a proliferative vasculopathy [4]. Poisoning, maternal hypoxia, the hypothesis of an aplastic process, and, finally, a fetofetal transfusion syndrome especially in monochorionic twins have been identified as further factors of relevance in the genesis of hydranencephaly [5].…”
Section: Introductionmentioning
confidence: 99%